Perlindungan Hukum Bagi Pemilik Kartu Elektronik dalam Transaksi E-Commerceputu - Widhiatmika Coryka; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Interpretasi Hukum, 2021)
Electronic contracts are one of the new forms of contracts that get special protection in Law Number 11 of 2008 concerning Information and Electronic Transactions. In general, electronic contracts are very different from ordinary (conventional) forms of contract, therefore it will be very difficult to directly apply the conditions for the occurrence of conventional contracts to this electronic contract (online contract). The purposes of this study are to reveal the validity of electronic contracts in credit card agreements and legal protection for credit card owners in e-commerce transactions. This research was conducted using normative legal research by applying a statutory approach. The technique of collecting legal materials is carried out by taking inventory of laws and regulations and recording techniques. This study uses primary and secondary legal materials which are then processed using deductive logic with analysis of legal interpretation and legal arguments presented descriptively. The results of the study reveal that in Law Number 8 of 1999 there are regulations that protect the parties who carry out E-Commerce transactions. Electronic contracts are basically the same as written contacts and have legal force and legal consequences as long as they meet statutory requirements. The legal protection provided by Article 26 of Law Number 8 of 1999 provides protection for consumers by requiring business actors who trade services to fulfill the agreed or/or agreed guarantees and/or guarantees.